2020
DOI: 10.13057/biodiv/d210918
|View full text |Cite
|
Sign up to set email alerts
|

Prope legitimate rootstocks determine the selection criteria for drought-tolerant cocoa

Abstract: Abstract. Zasari M, Wachar A, Susilo AW, Sudarsono. 2020. Prope legitimate rootstocks determine the selection criteria for drought-tolerant cocoa. Biodiversitas 21: 4067-4075. Drought tolerant cocoa seedlings are needed for the success of cocoa cultivation under drought conditions. Prope legitimate rootstock is feasible to be used in the selection of drought-tolerant cocoa seedlings. This objective of this study was to determine the selection criteria and tolerance of prope legitimate cocoa rootstocks in respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
4
0
2
Order By: Relevance
“…These results implied that Chinese softneck which was nonbolting types garlic would require a relatively short period and a higher temperature in the vernalization treatment than other garlic genotypes to break the bulb dormancy. Generally, the sensitivity index can be used to select genotypes that are tolerant to environmental stress (Zasari et al, 2020). That statement showed that the Chinese softneck most likely has a low tolerance to cold temperature stress.…”
Section: Sensitivity Of Garlic Genotypes To Low Temperature (Vernaliz...mentioning
confidence: 99%
“…These results implied that Chinese softneck which was nonbolting types garlic would require a relatively short period and a higher temperature in the vernalization treatment than other garlic genotypes to break the bulb dormancy. Generally, the sensitivity index can be used to select genotypes that are tolerant to environmental stress (Zasari et al, 2020). That statement showed that the Chinese softneck most likely has a low tolerance to cold temperature stress.…”
Section: Sensitivity Of Garlic Genotypes To Low Temperature (Vernaliz...mentioning
confidence: 99%
“…Karakter yang memiliki keragaman genetik yang sempit umumnya akan memiliki keragaman fenotipe yang sempit. Keragaman genetik merupakan salah satu faktor yang mempengaruhi keragaman fenotipe tanaman (Devy et al, 2018;Zasari et al, 2020).…”
Section: Karakter Kuantitatif Kopi Robusta Lokal Bangkaunclassified
“…legitimate seeds from open pollination of a female parent whose identity is identified and a male parent growing close together. The cocoa rootstock is generally obtained from prope legitimate seeds that are easily and quickly produced into seedlings (Zasari et al, 2020).…”
Section: Physio-biochemical Characteristics Of Prope Legitimatementioning
confidence: 99%
“…The stomata of the abaxial part of the leaf were observed under a microscope with 10 times magnification, and the density was counted. RWC was determined at the Agronomy Laboratory of Puslitkoka Jember, Indonesia (Zasari et al, 2020).…”
Section: Measurement Of Stomatal Density Rwc and Proline Contentmentioning
confidence: 99%